Dampak Media Sosial Terhadap Regulasi Emosi Mahasiswa Pada Program Studi Bimbingan Penyuluhan Islam - Azzahra, Hanan Sarah; Nasichah, Nasichah; Sulistira, Agis Nur Fazhan; Septiani , Putty Anggie (DIKLINKO JOURNALS PUBLISHER, 2023)
Social media is one of the very easy social tools that can have both positive and negative impacts. The impacts that may occur include feeling anxious, overthinking, and even the possibility of addiction, which can make adolescents struggle to control their emotions. If this happens continuously, it can be dangerous for mental health, especially in controlling emotions. This research aims to examine the mental health of students in the Islamic Counseling and Guidance UIN Syarif Hidayatullah Jakarta regarding emotional mental health in adolescents. This research uses a qualitative case study method that shows students with low emotional regulation abilities tend to use social media to reduce the pressure they experience, leading to potential addiction if such behavior continues. Students with high emotional regulation tend to avoid social media addiction because they engage in other activities that regulate their emotions effectively.